(untitled) (Research, Society and Development, 2021)
The aim of the present study was to investigate, through a systematic review, the effects of caffeine use on the individual in HIIT sessions. After selecting articles in the Medline / PubMed, Science Direct, scholar google and Scielo databases, 2301 studies were found. After applying the inclusion and exclusion criteria, only five articles were considered eligible for systematic review. Among these studies, the total number of participants was 80 individuals, 24 women and 56 men, aged between 18 and 30 years. The protocols used consisted of two types: acute and chronic, assessing anthropometric and / or metabolic parameters. In experiments that used a chronic approach, results were found favorable to the loss of body fat and improvement of metabolic indexes. On the other hand, studies with an acute approach observed an improvement in performance through the delay of muscle fatigue, however, without significant difference in body mass at the end of the session. Still, one of the studies with chronic intervention did not observe a significant difference between the groups. Caffeine associated with HIIT can bring benefits to the individual, regardless of their physical condition. However, further studies are needed to better understand the extent and condition of these benefits.